Renal thrombotic microangiopathy in an ANCA-associated vasculitis - Ana Teresa Domingos; Sara Barreto; Eduarda Carias; Ana Cabrita; Helena Viana; Mário Góis (Society of Diabetic Nephropathy Prevention, 2019)
Anti-neutrophil cytoplasmic antibody (ANCA) disease remains a diagnostic challenge due to the heterogeneity of possible clinical presentations. We present the case of a 63-year-old white male with a known history of ANCA-associated vasculitis (AAV) with anti-myeloperoxidase antibodies (MPO) - mainly with respiratory manifestations - treated with corticosteroids and cyclophosphamide, resulting in partial improvement. Six months later he was referred to the nephrology department for rapidly progressive renal failure and a kidney biopsy was performed, which showed several glomeruli globally sclerosed and others presenting fibrous crescents. Vascular involvement was also noted with several small arteries revealing endothelial swelling and entrapped erythrocytes within a fibrin thrombus. Immunofluorescence was negative. A high percentage of parenchymal fibrosis and no evidence of active extra-renal manifestations dictated no specific treatment. The patient is currently monitored in a low clearance nephrology consultation. Evidence of thrombotic microangiopathy (TMA) is an uncommon histological finding in kidney biopsies of patients with AAV, being associated with worst prognosis.